alvarez01
alvarez01
02-07-2018
Mathematics
contestada
if f(x)=3x-5 and g(x)=x+3 find (f-g)(x)
Respuesta :
mkryukova19
mkryukova19
02-07-2018
f(x)=3x-5
g(x)=x+3
(f-g)(x)
=
3x-5 -(x+3)= 3x - 5 -x -3 =
2x-8
(f-g)(x)=2x - 8
Answer Link
VER TODAS LAS RESPUESTAS ( 75+ )
Otras preguntas
if more than one sperm cell were able to enter an egg, what might be the result?
Why doesn't Odysseus clasp Nausicaa's knees?
Verona is solving the equation -3 + 4x = 9. In order to isolate the variable term using the subtraction property of equality, which number should be subtracted
the simplest particles of iron are
what are the benefits of genetic variation?
Multiply the polynomials (5x^2+4x-4)(4x^3-2x+6) Explain your steps!!
mr. Fields ordered 3 tons of gravel for driveway at a factory how many pounds of gravel did he order
three of the following are features of absolutism. which is not
Why were some Serbians and Bosnians angry with Austria-Hungary in 1914?
What is the source of energy for our weather?